Systematic literature review of the burden and outcomes of infections due to multidrug-resistant organisms in Europe: the ABOUT-MDRO project protocol. Issue 5 (5th May 2020) - Anaya-Baz, Blanca; Maldonado, Natalia; Palacios-Baena, Zaira R; Palomo, Virginia; Pezzani, Maria Diletta; Chiesi, Sheila; Razzaboni, Elisa; Compri, Monica; Tacconelli, Evelina; Rodriguez-Baño, Jesús
Abstract : Introduction: Despite the increasing importance of infections due to multidrug-resistant organisms (MDROs), there is a lack of comprehensive information about the burden of disease and outcomes of key infections caused by these pathogens. The aim of the ABOUT-MDRO (A systematic review on the burden and outcomes of infections due to multidrug resitant organisms) project is to provide estimations of the burden of some key infections and their outcomes caused by the target MDROs. Methods and analysis: A systematic literature search will be performed using MEDLINE/PubMed, Elsevier's SCOPUS, Cochrane library, Clinical trials and Web of Science, as well as the Surveillance Systems from Public Health Institutions and Scientific Societies for Antimicrobial Resistance and Healthcare-Associated Infections in Europe database of European surveillance systems, for data on prevalence/incidence, mortality and length of stay of target infections in hospitalised patients (including ventilator-associated pneumonia, hospital-acquired pneumonia, complicated intra-abdominal infections, complicated urinary tract infections, skin and soft tissue infections and bloodstream infections) and in specific populations (children, hospital wards, neutropenic patients) caused by cephalosporin-resistant or carbapenem-resistant Enterobacteriaceae, carbapenem-resistant Pseudomonas aeruginosa and Acinetobacter spp., methicillin-resistant Staphylococcus aureus, and vancomycin-resistant Enterococcus spp. The information retrieved will be tabulated and pooled estimates and 95% CIs calculated of rates and outcomes, using random effects models. Relationships between rates and outcomes in randomised control trials and epidemiological studies, and data of proportions and incidence/prevalence rates will also be analysed. The information collected in this study will be useful for identifying gaps in our knowledge in terms of incidence/prevalence and clinical outcomes of infections caused by MDROs, and for informing priorities in infection control and the research and design of appropriate studies. Ethics and dissemination: This study will be based on published data so we did not require ethical approval. Formal consent is not required. The results of this review will be reported according to the Preferred Reporting Items for Systematic Review and Meta-Analyses statement. Data will be presented at international conferences and published in peer-reviewed journals. Registration details: PROSPERO (https://www.crd.york.ac.uk/prospero/ ) (CRD42019124185).